2022
DOI: 10.1002/adma.202106682
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Triggered Efficient Sequential Drug Delivery of Biomimetic Nanosystem for Multimodal Chemo‐, Antiangiogenic, and Anti‐MDSC Therapy in Melanoma

Abstract: In view of the multiple pathological hallmarks of tumors, nanosystems for the sequential delivery of various drugs whose targets are separately located inside and outside tumor cells are desired for improved cancer therapy. However, current sequential delivery is mainly achieved through enzyme‐ or acid‐dependent degradation of the nanocarrier, which would be influenced by the heterogeneous tumor microenvironment, and unloading efficiency of the drug acting on the target outside tumor cells is usually unsatisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…1,2 In the case of superficial tumors such as head and neck squamous cell carcinoma (HNSCC), near-infrared (NIR) light responsive PTT is preferable due to effective photo penetration. [3][4][5] Besides direct damage to cancer cells, PTT has also been shown to promote immunogenic cell death (ICD), a process that causes cancer cells to release tumor-associated antigens, which further trigger the anti-tumor immune response, 6,7 generating the cytotoxic T lymphocytes (CTLs) to eliminate residual tumor cells and inhibit its metastasis. 8 Until now, many PTT studies of oncotherapy based on various photothermal agents (PTAs) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the case of superficial tumors such as head and neck squamous cell carcinoma (HNSCC), near-infrared (NIR) light responsive PTT is preferable due to effective photo penetration. [3][4][5] Besides direct damage to cancer cells, PTT has also been shown to promote immunogenic cell death (ICD), a process that causes cancer cells to release tumor-associated antigens, which further trigger the anti-tumor immune response, 6,7 generating the cytotoxic T lymphocytes (CTLs) to eliminate residual tumor cells and inhibit its metastasis. 8 Until now, many PTT studies of oncotherapy based on various photothermal agents (PTAs) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Constructing biomimetic DDSs by bioorthogonal chemistry Biomimetic techniques to enable precise drug delivery has become a research focus. [188][189][190][191] The use of natural cell membranes to cover nanoparticles avoids immune system clearance while keeping innate targeting capabilities. The majority of the targeting effects of cell membrane-based biomimetic DDSs are mediated by cytokines or chemokines.…”
Section: Application Of Bioorthogonal Chemistry In Developing Bio-ins...mentioning
confidence: 99%
“…Then, the other drug, along with the nanocarrier, is internalized into cells for the intracellular target treatment [ 73 ]. As shown in Figure 4 C, Lai and co-workers [ 71 ] proposed a sequential delivery strategy which mainly relies on a light-responsive liposomes encapsulated with sunitinib [ 74 ] (antiangiogenic inhibitor for multiple cancers).…”
Section: Drug Delivery In Vivomentioning
confidence: 99%